2020
DOI: 10.2147/ceor.s252244
|View full text |Cite
|
Sign up to set email alerts
|

<p>Socioeconomic Inequality in Self-Medication in Iran: Cross-Sectional Analyses at the National and Subnational Levels</p>

Abstract: Background: Self-medication (SM) is a public health concern globally. This study aimed to measure socioeconomic inequality in SM and identify its main determinants among Iranian households. Methods: A total of 38,859 households from the 2018 Household Income and Expenditure Survey (HIES) were included in the study. Data on SM, household size, age, gender and education status of the head of household, monthly household's expenditures (as a proxy for socioeconomic status), health insurance coverage and living ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
3
1
Order By: Relevance
“…The concentration index also revealed an inequality in favor of the poor in non-prescribed medicine use in Iran. This finding contrasts with a former Iranian study (20) that reported pro-rich socio-economic inequality in selfmedication in Iran. In previous research, authors used household budget data provided by the Statistics Center of Iran.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The concentration index also revealed an inequality in favor of the poor in non-prescribed medicine use in Iran. This finding contrasts with a former Iranian study (20) that reported pro-rich socio-economic inequality in selfmedication in Iran. In previous research, authors used household budget data provided by the Statistics Center of Iran.…”
Section: Discussioncontrasting
confidence: 99%
“…Another problem is international sanctions, which have had a negative impact on access to medicine in Iran. Although some studies investigated socio-economic inequality in self-medication (20) and even the use of herbal medicines (21), there is no evidence of socio-economic inequalities in prescribed medicine use in Iran. In this study, unlike previous studies, the required data was obtained from the healthcare utilization survey, which better shows the health-seeking behavior than the income and expenditure survey.…”
Section: Objectivesmentioning
confidence: 99%
“… NO Secondary data Original Article/ English 1995–2014 Iranian households Determinants of exposure to CHE: gross domestic production (GDP)(+), gross national production(+), national income(+), and national consumption countries income(+), Unemployment(+), liquidity rate(+), inflation rate(+), budget deficit(+), population rate(+). 47 Rezaei, Satar et al 2020 ( 102 ) Measure equity in OOP payments for healthcare and the incidence of CHE among Iranian households over time. Retrospective descriptive study (measurement) WHO method Trend series regression.…”
Section: Search String For Various Databasesmentioning
confidence: 99%
“…[ 14 15 16 17 ] Various studies have shown that self-medication is influenced by several factors, including age, sex, education level, marital status, socioeconomic status, health insurance coverage, place of residence, and availability of medications for individuals. [ 18 ]…”
Section: Introductionmentioning
confidence: 99%